Plant-Derived Alkaloids: The Promising Disease-Modifying Agents for Inflammatory Bowel Disease - Peng, Jiao; Zheng, Ting-Ting; Li, Xi; Liang, Yue; Wang, Li-Jun; Huang, Yong-Can; Xiao, Hai-Tao (Frontiers in Pharmacology, 2019)
Inflammatory bowel disease (IBD) represents a group of intestinal disorders with self-destructive and chronic inflammation in the digestive tract, requiring long-term medications. However, as many side effects and drug resistance are frequently encountered, safer and more effective agents for IBD treatment are urgently needed. Over the past few decades, a variety of natural alkaloids made of plants or medicinal herbs have attracted considerable interest because of the excellent antioxidant and anti-inflammatory properties; additionally, these alkaloids have been reported to reduce the colonic inflammation and damage in a range of colitic models. In this review paper, we summarise the recent findings regarding the anti-colitis activity of plant-derived alkaloids and emphasise their therapeutic potential for the treatment of IBD; obvious improvement of the colonic oxidative and pro-inflammatory status, significant preservation of the epithelial barrier function and positive modulation of the gut microbiota are the underlying mechanisms for the plant-derived alkaloids to treat IBD. Further clinical trials and preclinical studies to unravel the molecular mechanism are essential to promote the clinical translation of plant-derived alkaloids for IBD.